THE INFLUENCE OF PRINCIPAL LEADERSHIP ROLE AND TEACHER PROFESSIONALISM IN IMPROVING TEACHER PERFORMANCE IN MATARAM CITY WITH EDUCATIONAL QUALITY MANAGEMENT AS A MEDIATION VARIABLE - Jayadi, Usman; Farida Ferine, Kiki; Alfahmi, Muhammad (CV. Lafadz Jaya, 2025)
This study aims to explore the influence of school leadership and teacher professionalism on the improvement of teacher performance in Mataram City, with educational quality management as a mediating variable. The research employs a quantitative approach and uses purposive sampling techniques. Data were collected from all respondents, grouped according to established criteria, tested on each variable, and analyzed using the Partial Least Squares (PLS) method. The results show that the first hypothesis, which states that there is an influence of school leadership on educational quality, is rejected. The second hypothesis, indicating that teacher professionalism affects educational quality, is accepted. The third hypothesis, stating that school leadership impacts teacher performance, is also accepted. The fourth hypothesis, which asserts that teacher professionalism influences teacher performance, is accepted. However, the fifth hypothesis, which indicates the effect of educational quality on teacher performance, is rejected. Conversely, the sixth hypothesis, stating that school leadership significantly influences teacher performance through educational quality, is rejected. In contrast, the seventh hypothesis, indicating that teacher professionalism affects teacher performance through educational quality, is accepted.